Perancangan Data Warehouse Untuk Pasien Rawat Inap Pada Rumah Sakit Siti Fatimah Az-Zahra - Hafiz, Dio; Rahman, Abdul (MDP Student Conference, 2024)
Data warehouse is a method used to accommodate and analyze large amounts of data. This analysis can be viewed from several different dimensions or points of view. Analysis and design using Tableau to visualize and create an information dashboard, succeeded in helping both in detail and in summary according to needs, and information can be accessed more quickly and easily to support decision making for hospital leaders. The purpose of writing this thesis This is to build a data warehouse that can store data in an organized manner and make it easier to analyze data to make decisions. The method used is the Nine-step Methodology which consists of 9 stages, namely Process Selection, Grain Selection, Dimension identification and adjustment, Fact Selection , Storing precalculations in fact tables, Confirming dimension tables, Selecting database duration, Tracking changes in dimensions slowly, Determining priorities and query models. The results achieved in designing the data warehouse at Fatimah Az-Zahra Hospital in Palembang are that it can display patient visualizations based on specified dimensions, namely the patient's gender, date of inpatient admission, diagnosis results, discharge condition.